Future Development of Social Interest Housing Market in Mexico: Homex, Developer of Housing - Vargas-Hernández, José G; Akihito, Hayashi Vega Oscar (Journal of Asian Business Strategy, 2014)
Before the 2009 crisis, the change in the economic environment in policies support housing sector and regulations implemented by the federal government in the years following, significantly changed the environment in which construction companies were operating housing, which directly affected the business model adopted by public developers, so having to restructure their construction processes, and adapt to new trends that are expected to improve the quality of life of consumers. It is important to perform an analysis of the business situation, the structure of this market with industry and to future decision-making strategies.